2022
DOI: 10.1038/s41598-022-09360-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of psychosocial stress on plan based movement selection

Abstract: Efficient movement selection is crucial in everyday activities. Whether this function is governed by our stress system is so far unknown. In the current study, data from thirty-six young male adults were analyzed. They performed rule- and plan-based movement selection tasks before (session 1) and after (session 2) a psychosocial stressor, or after a control condition without additional social stressor. Results showed that the rule-based efficiency advantage which was observed prior to the psychosocial stressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…If-then rules (in some contexts referred to as Implementation Intentions) have been shown to facilitate many cognitive tasks (Gollwitzer and Sheeran, 2006;Wieber et al, 2015). Several motor cognitive studies have demonstrated that using such rules leads to shorter action initiation latency and reduced error rates compared to using a prospective planning approach when producing the same actions (Randerath et al, 2013(Randerath et al, , 2015(Randerath et al, , 2017Scheib et al, 2018;Stoll et al, 2022b). It has been hypothesized that rule-based action selection may have the potential to be particularly effective in improving the successful selection of grips in persons with difficulties in prospective planning.…”
Section: Introductionmentioning
confidence: 99%
“…If-then rules (in some contexts referred to as Implementation Intentions) have been shown to facilitate many cognitive tasks (Gollwitzer and Sheeran, 2006;Wieber et al, 2015). Several motor cognitive studies have demonstrated that using such rules leads to shorter action initiation latency and reduced error rates compared to using a prospective planning approach when producing the same actions (Randerath et al, 2013(Randerath et al, , 2015(Randerath et al, , 2017Scheib et al, 2018;Stoll et al, 2022b). It has been hypothesized that rule-based action selection may have the potential to be particularly effective in improving the successful selection of grips in persons with difficulties in prospective planning.…”
Section: Introductionmentioning
confidence: 99%